STRATEGI PROMOSI UNTUK MENJAGA HUBUNGAN DENGAN WISATAWAN DI KAWASAN WISATA KUTA PADA ERA NEW NORMAL - Anak Agung Ananda Pradnya Pramitha; Hanugerah Kristiono Liestiandre; Dewa Ayu Made Lily Dianasari (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
This research aims to create an integrated promotional strategy to maintain relationships with tourists in Kuta tourism area in the new normal era. The strategy was formed using a reference from Customer Relationship Marketing (CRM). Customer Relationship Marketing (CRM) is a marketing activity that aims to find, establish and maintain relationships with customers. Data collection techniques are carried out through documentation, literature studies, observations and interviews. The sampling technique used is Purposive Sampling. The data obtained is analyzed using qualitative descriptive analysis techniques. Based on the research that has been done formed several strategies that can be used to maintain good relationships with tourists or customers. The strategies are grouped into 4 categories. The four categories are trust, commitment, communication and problem handling. In these circumstances maintaining a relationship with a traveler or customer is very important. The right strategy is needed so that when the tourism gate has reopened, then tourists or customers will not be reluctant to come visit.